2018
DOI: 10.5547/01956574.39.6.mhyl
|View full text |Cite
|
Sign up to set email alerts
|

Firm-level Estimates of Fuel Substitution: An Application toCarbon Pricing

Abstract: We estimate partial-and total-fuel substitution elasticities between electricity, gas and oil, using firm-level data. We find that, based on the partial elasticity measure, electricity is the least-responsive fuel to changes in its own price and in the price of other fuels. The total elasticity measure, which adjusts the partial elasticity for changes in aggregate energy demand induced by individual fuel price changes, reveals that the demand for electricity is much more price responsive than the partial elast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 37 publications
2
7
0
Order By: Relevance
“…These elasticities are smaller than previous estimates based on firm-level data. For example, in an earlier study of factor substitution in Irish manufacturing, Hyland and Haller (2018) estimate an own-price elasticity of demand for capital of -0.62; which is similar to that reported for Italian manufacturing firms by Bardazzi et al (2015) based on the average estimated across all manufacturing firms. It is important to emphasize that a direct comparison with other estimates is not entirely appropriate.…”
Section: System Estimation Resultssupporting
confidence: 61%
See 1 more Smart Citation
“…These elasticities are smaller than previous estimates based on firm-level data. For example, in an earlier study of factor substitution in Irish manufacturing, Hyland and Haller (2018) estimate an own-price elasticity of demand for capital of -0.62; which is similar to that reported for Italian manufacturing firms by Bardazzi et al (2015) based on the average estimated across all manufacturing firms. It is important to emphasize that a direct comparison with other estimates is not entirely appropriate.…”
Section: System Estimation Resultssupporting
confidence: 61%
“…Finding an appropriate firm-level panel dataset to illustrate the model is a daunting task as almost all inter-fuel substitution literature is based on highly aggregated data (Steinbuks, 2012). While we do not have perfect data with which to estimate the model, the availability of rich firm-level panel data of manufacturing firms in the Republic of Ireland, one of the most comprehensive datasets used in the capital-energy nexus literature to date (see e.g., Haller and Hyland, 2014;Hyland and Haller, 2018), provides a useful resource to illustrate the implementation of our model. These data are collected by the Irish Central Statistics Office (CSO) via the annual Census of Industrial Production (CIP).…”
Section: Overviewmentioning
confidence: 99%
“…The first novelty is methodological, as we illustrate the advantages of a cointegrating approach applied on a system of fuel shares, which has been previously applied only once but for the industrial sector as a whole rather than the industrial subsectors modelled in the study. By implementing the first cointegration analysis for a set of fuels shares estimated at a disaggregated industrial level, we showed that plausible and robust estimates of price elasticities can be obtained Bardazzi et al (2016) -0.82 Italy Burke and Yang (2016) (-1.09, -1.00) International Enevoldsen et al 2007-0.11 Nordic countries Harvey and Marshall (1991) -0.62 UK Huntington (2007) (-0.29, -0.15) US Hyland and Haller 2018-1.16 Ireland Pindyck (1979) -1.44 UK Renou-Maissant (1999) -0.65 UK Serletis et al 2010-0.13 UK Serletis and Shahmoradi (2008) (-1.50, -1.01) US Steinbuks 2012(-0.94, -0.28) Long-run, UK, heating and all processes respectively Suh 2016-0.20 US Taheri and Stevenson (2002) -0.39 US Uri (1979) -082 UK Uri (1982) -0.91 UK Westoby (1984) -1.06 UK Our weighted average -1.22 UK Enevoldsen et al (2007) (-0.28, -0.10) Nordic countries Harvey and Marshall (1991) -0.06 UK Hyland and Haller (2018) -0.31 Ireland Jamil and Ahmad (2011) -1.22 Long-run, Pakistan Paul et al (2009) -0.40 US Pindyck (1979) -0.56 UK Renou-Maissant (1999) -0.31 UK Ros (2015) (-0.87, -0.52) Long-run, US Serletis et al 2010-0.004 UK Steinbuks (2012) (-1.11, -0.23) Long-run, UK, heating and all processes respectively Suh 2016-0.11 US Taheri and Stevenson (2002) -0.71 US Uri (1979) -0.22 US Uri (1982) -0.50 UK Westoby (1984) -0.39 UK Our weighted average -0.82 UK even from relatively short time series using a parsimonious but careful application of a system approach. Modelling a VECM for each of the eight industrial subsectors we obtained unequivocal evidence for the existence of two cointegrating relationships representing demand for electricity and gas.…”
Section: Discussionmentioning
confidence: 99%
“…. Hyland and Haller (2018) typically feature such price elasticities between electricity, gas and oil using firm-level data.…”
Section: A Dynamic Panel Data Modelingmentioning
confidence: 99%